MANAJEMEN KEPEMIMPINAN KEPALA MADRASAH BERBASIS KETELADANAN DAN MUSYAWARAH DALAM MENINGKATKAN DISIPLIN GURU:STUDI KASUS DI MA DAARUL HUDA LITAHFIDHIL QUR'AN MALANG - Miftahul Hamida; Muhammad Husni (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to describe and analyze the leadership management of the madrasah principal grounded in exemplary leadership (uswah hasanah) and consultative leadership (musyawarah/shura) and its impact on improving teacher discipline at MA Daarul Huda Litahfidhil Qur'an Malang. A qualitative approach with a single case study design was employed. Data were collected through participatory observation, in-depth interviews with the principal, vice principals, senior teachers, junior teachers, and educational staff, as well as document analysis over approximately two months. The findings reveal that the principal implements exemplary leadership through three key dimensions: (1) punctuality by arriving before teachers; (2) religious exemplarity through active participation as congregational prayer leader and Tahfidz Al-Qur'an program participant; and (3) professional work ethic and egalitarian social interaction. Consultative leadership is implemented through a structured forum system—daily, weekly, monthly, and annual meetings—which has evolved into an organizational culture of the madrasah. The integration of both leadership patterns produced measurable impacts: improved teacher attendance discipline, enhanced affective commitment in carrying out duties, and the growth of collective responsibility grounded in Islamic values. This study affirms that Islamic values-based leadership management—particularly uswah hasanah and shura—is empirically effective in building a culture of discipline in Islamic educational institutions.